The Blueprint : Conservative Parties and their Impact on canadian Politics. - Lewis, J. P. (University of Toronto Press, 2017)
In this collection, J.P. Lewis and Joanna Everitt bring together a group of up-and coming-political scientists as well as senior scholars to explore the recent history of the Conservative Party of Canada, covering the pre-merger period (1993-2003) and both the minority and majority governments under Prime Minister Stephen Harper.
Keywords: Conservative Party of Canada ( -1942); Parti conservateur du Canada.; Conservatism -- Canada.; Canada -- Politics and government -- 1993-2006.; Conservatisme -- Canada.; POLITICAL SCIENCE -- Political Process -- Elections.; POLITICAL SCIENCE -- Political Process -- General.; POLITICAL SCIENCE / History & Theory; Conservatism; Canada; Electronic books.